Climate Information Service Advisories for Major Field Crops of Bangladesh ( "Agvisely") linked to the Department of Agricultural Extension (DAE) and the Bangladesh Meteorological Department (BMD) portals - CGIAR Research Program on Maize (2019)
In November 2019, it was agreed that Agvisely would be linked on the Bangladesh Meteorological Department (BMD) website on an experimental basis, to allow users to access climate advisories.